Analisis Pengaruh Campuran Bioaditif Cengkeh Pada Bahan Bakar Pertalite Terhadap Performa Mesin Motor 4 Tak - Hermanto, Tino; Pratama, Wahyu; Idris, Muhammad; ., Rahmatullah (Fakultas Teknik UMSU, 2023)
Bio additives are substances from nature that are combined with other substances to perform specific tasks, such as lowering exhaust emissions, preventing corrosion, and increasing engine efficiency. Therefore, the purpose of this study was to determine how the effect of adding bio additives to pertalite fuel on the performance of a 4 TAK motorcycle engine. Clove oil is the bioadditive used in this study. The experimental strategy was used in this study to approach the research by reading books and magazines. This research was conducted at PT. Indako Trading which is located in Siti Rejo I, Kec. Medan City, Jl. Sisingamangaraja No. 362, Medan City, North Sumatra 20144. In this experiment, different ratios of pertalite and bio additive fuels were used, including pure pertalite fuel 2:1000 ml, 5:1000 ml, 10:1000 ml, and 1000 ml. From the results of the tests carried out in this study, there was an increase in the power and torque values of the motorcycle, with the highest power and torque values of 0.4 kW and 0.4 Nm, respectively, in the comparison of variations in the mixture of bioadditives and pertalite of 5:1000 ml and 1000 ml of pure pertalite.